Association between the aldehyde dehydrogenase 2*2 allele and smoking-related chronic airway obstruction in a Japanese general population: A pilot study. Issue 2 (16th July 2015) - Morita, Kazunori; Masuda, Natsuki; Oniki, Kentaro; Saruwatari, Junji; Kajiwara, Ayami; Otake, Koji; Ogata, Yasuhiro; Nakagawa, Kazuko
Highlights Aldehyde dehydrogenase 2 (ALDH2) may protect airways against cigarette smoke injury. ALDH2*2 allele and ever smoking affected airway obstruction in a dose-dependent manner. Pack-years smoking was a predictor of airway obstruction only in *2 allele carriers. *2 allele is associated with the incidence of smoking-related airway obstruction. Combined effect of smoking and *2 allele was prominent in the asthmatic subjects.